RESPONSE OF LOCAL SWEET ORANGE TRANSPLANTS TO SPRAYING WITH MICRONUTRIENTS AND CPPU - A. F. Z. Al-Dulaimy; O. A. J. Mohammed (مجلة الأنبار للعلوم الزراعية)
The experiment was carried out in Lath house belonging to Department of Horticulture and Landscape Gardening at College of Agriculture - University of Anbar for period 15/8/2022 to 1/6/2023, to study effect of spraying with each of combination of micronutrients Fe, Zn and Mn at a concentrations (0, 0.25 and 0.50 g L-1), which are symbolized by symbols (M0, M1 and M2), respectively, and spraying with growth regulator CPPU at concentrations (0, 6 and 12 mg L-1) which are symbolized by symbols (C0, C1 and C2), respectively. on some vegetative growth traits of Local Sweet Orange transplants. A two-factor experiment (3 × 3) was carried out according to a randomized complete block design (R.C.B.D). The experiment included 9 treatments, 108 uniform transplants were selected in their growth as much as possible as 3 replications, and 4 transplant for each experimental unit.Spraying with combination of micronutrients had a significant effect on all studied traits, especially the high level (M2), which achieved best values for traits (increased of saplings 61.25 cm, shoot of lengths 32.20 cm sapling height, rootstock stem diameter increment 6.27 mm, scion stem diameter increment 3.48 mm, increased of leaves number of 60.43 leaf sapling-1, The dry weight of vegetative system 75.60 g, leaves area 1468.75 cm2 sapling-1. On the other hand, spraying with growth regulator (CPPU) showed significant effect on all traits except of increased of rootstock and scion diameter. Treatment (C2) achieved best significant effect of traits (increased of transplant height, shoot lengths, dry weight of vegetative system and leaves area) which amounted (55.49 cm, 31.56 cm, 73.42 g, 31.87 g, 1387.88 leaves sapling-1), respectively. Whereas, treatment (C1) showed the highest values for the trait (increased of leaves number 58.63 leaf transplant-1). The interaction of two study factors reached the level of significance in the effect on all the studied traits except the rate of the increase in the rootstock and scion diameter